Effects of ketogenic diet on cognitive function of patients with Alzheimer's disease: a systematic review and meta-analysis - Liyang Rong; Yating Peng; Qi Shen; Keying Chen; Bangjiang Fang; Weirong Li (Elsevier, 2024)
Background: Ketogenic diets (KD) have shown remarkable effects in many disease areas. It has been demonstrated in numerous animal experiments that KD is effective in the treatment of Alzheimer's disease (AD). But the clinical effect of treating AD is uncertain. Objective: To systematically review the impact of KD on cognitive function in AD. Methods: We conducted a search of three international databases-PubMed, Cochrane Library, and Embase-to retrieve RCTs on the KD intervention for AD from the inception of the databases through October 2023. Two reviewers searched and screened the literature, extracted and checked relevant data independently, and assessed the risk of bias of the included studies. The meta-analysis was carried out utilizing RevMan 5.3 software. Results: A total of 10 RCTS involving 691 patients with AD were included. There were 357 participants in the intervention group and 334 participants in the control group. The duration of the KD intervention ranged from a minimum of 3 months to a maximum of 15 months. Meta-analysis results showed that KD could effectively improve the mental state of the elderly (NM scale) [MD = 7.56, 95%CI (3.02, 12.10), P = 0.001], MMSE [MD = 1.25, 95%CI (0.46, 2.04), P = 0.002], and ADAS-Cog [MD = −3.43, 95%CI (−5.98, −0.88), P = 0.008]. The elevation of ketone body (β-hydroxybutyric) [MD = 118.84, 95%CI (15.20, 222.48), P = 0.02] may also lead to the elevation of triglyceride [MD = 0.19, 95%CI (0.03, 0.35), P = 0.02] and low density lipoprotein [MD = 0.31, 95%CI (0.04, 0.58), P = 0.02]. Conclusion: Research conducted has indicated that the KD can enhance the mental state and cognitive function of those with AD, albeit potentially leading to an elevation in blood lipid levels. In summary, the good intervention effect and safety of KD are worthy of promotion and application in clinical treatment of AD.